Building resilience and greening the economy: Integrating climate, peace, and security into Zambia’s capacity to adapt to climate change - Caroli, Giulia; De Coning, Cedric; Kinnes, Shaun; Maviza, Gracsious (2024)
Finding the right balance between adaptation and mitigation.